15% Efficiency Tandem Organic Solar Cell Based on a Novel Highly Efficient Wide‐Bandgap Nonfullerene Acceptor with Low Energy Loss. Issue 11 (28th January 2019) - Liu, Gongchu; Jia, Jianchao; Zhang, Kai; Jia, Xiao'e; Yin, Qingwu; Zhong, Wenkai; Li, Li; Huang, Fei; Cao, Yong
Abstract: A tandem organic solar cell (OSC) is a valid structure to widen the photon response range and suppress the transmission loss and thermalization loss. In the past few years, the development of low‐bandgap materials with broad absorption in long‐wavelength region for back subcells has attracted considerable attention. However, wide‐bandgap materials for front cells that have both high short‐circuit current density ( J SC ) and open‐circuit voltage ( V OC ) are scarce. In this work, a new fluorine‐substituted wide‐bandgap small molecule nonfullerene acceptor TfIF‐4FIC is reported, which has an optical bandgap of 1.61 eV. When PBDB‐T‐2F is selected as the donor, the device offers an extremely high V OC of 0.98 V, a high J SC of 17.6 mA cm −2, and a power conversion efficiency of 13.1%. This is the best performing acceptor with such a wide bandgap. More importantly, the energy loss in this combination is 0.63 eV. These properties ensure that PBDB‐T‐2F:TfIF‐4FIC is an ideal candidate for the fabrication of tandem OSCs. When PBDB‐T‐2F:TfIF‐4FIC and PTB7‐Th:PCDTBT:IEICO‐4F are used as the front cell and the back cell to construct tandem solar cells, a PCE of 15% is obtained, which is one of best results reported to date in the field of organic solar cells. Abstract : A novel wide‐bandgap nonfullerene acceptor TfIF‐4FIC is synthesized. PBDB‐T‐2F:TfIF‐4FIC‐based organic solar cell acquires a power conversion efficiency (PCE) of 13.1%, a high open‐circuit voltage of 0.98 V, which is the best performed device with bandgap larger than 1.60 eV. When using PBDB‐T‐2F:TfIF‐4FIC as front cell and PTB7‐Th:PCDTBT:IEICO‐4F as back cell to construct tandem device, PCE of 15% is achieved.